Branch Retinal Artery Occlusion following Dental Extraction. (15th December 2014) - Oğurel, Tevfik; Onaran, Zafer; Oğurel, Reyhan; Örnek, Nurgül; Büyüktortop Gökçınar, Nesrin; Örnek, Kemal
Abstract : Aim . To describe a case of branch retinal artery occlusion following dental extraction and to point out the ophthalmic complications of dental procedures to ophthalmologists and dentists. Case . A 51-year-old woman was referred to our clinic with painless sudden visual loss in her left eye after tooth extraction two days ago. In her left eye the best corrected visual acuity was 6/30 and fundus examination revealed peripapillary flame-shaped hemorrhages and pale retina in the upper temporal arcuate. The right eye examination was unremarkable. Conclusion . Dental procedures can lead to miscellaneous ophthalmic complications possibly due to the close proximity of the anatomic structures. Retinal arterial occlusion is a rare but serious cause of permanent visual loss among these dental procedures where the exact pathologic mechanism is still obscure.